Citizenship Education as Legal Education in Schools - Siregar, Hotma; Kemala, Vinna Dinda (Lembaga Riset Mutiara Akbar, 2023)
Currently there are many cases of law violations committed by a student. This is considered as low legal knowledge possessed by students. Legal education in Citizenship Education basically plays a role in teaching law to students so they have legal awareness. Through this legal education, students have legal will, so they are able to control and filter out acts that violate the law, and have the ability to obtain legal protection. This also has implications for fulfilling the role of students in carrying out their rights and obligations as part of society in carrying out social control. Substantially, elements of legal education and citizenship education are correlated with development literacy and citizens' legal awareness. These elements include subject matter, instructional practice and context, skills and attitudes, beliefs, and values. These elements are the main aspects that are in line with the three main elements of citizenship education which include affective, cognitive, and psychomotor development. The concept of legal education in Citizenship Education is comprehensively integrated into the learning component of Citizenship Education. These components are integrated in the development of legal education which is based on the context of a reconstructive educational philosophy which places Pancasila as the central value